The Concept of Holiness of Catholic Young People - Yoyok Hardianto; Aloysius Gonzaga Ristata Kusnar P (CV. Rayyan Dwi Bharata, 2022)
Young Catholics sometimes do not realize that what they are doing is actually one of the characteristics of leading to holiness in this day and age that begins from receiving the baptism of their lives directed at holiness. Young Catholics are called to grow in holiness which according to Gaudete et Exultate there are several characteristics to lead to holiness. The purpose of this study was to find out the concepts of understanding of Young Catholics in the Mlese Region, Jombor Klaten Parish. This study uses Pope Francis' Apostolic call